Visual Search for Dimensionally Redundant Pop-Out Targets: Parallel-Coactive Processing of Dimensions Is Location Specific. - Krummenacher, Joseph; Müller, Hermann J.; Heller, Dieter (Journal of Experimental Psychology. Human Perception & Performance, 2002)
Three visual search experiments investigated redundancy gains for single and dual odd–one–out feature targets that differed from distractors in orientation, color, or both. In Experiment 1, redundant-target displays contained (a) a single target defined in 2 dimensions, (b) dual targets each defined in a different dimension, or (c) dual targets both defined in the same dimension. The redundancy gains, relative to single nonredundant targets, decreased from the first condition on, with violations of J. Miller's (1982) race model inequality (RMI) manifested only in the first 2 conditions. Experiment 2 systematically varied the spatial separation between dual targets each defined in a different dimension. Violations of the RMI were evident only when the 2 targets occupied nearby locations. Experiment 3 provided evidence of RMI violations by dimensionally redundant targets at both precued (likely) and noncued (unlikely) display locations. Taken together, these results suggest that there is coactivation of a common mechanism by target signals in different dimensions (not by signals in the same dimension), that the coactivation effects are spatially specific, and that the coactivated mechanisms are located at a preattentive, perceptual stage of processing. Reprinted by permission of the publisher.